Extracellular Vesicles Derived From Adult and Fetal Bone Marrow Mesenchymal Stromal Cells Differentially Promote ex vivo Expansion of Hematopoietic Stem and Progenitor Cells - Ghebes, Corina A.; Morhayim, Jess; Kleijer, Marion; Koroglu, Merve; Erkeland, Stefan J.; Hoogenboezem, Remco; Bindels, Eric; van Alphen, Floris P. J.; van den Biggelaar, Maartje; Nolte, Martijn A.; van der Eerden, Bram C. J.; Braakman, Eric; et al. (Frontiers in Bioengineering and Biotechnology, 2021)
Recently, we and others have illustrated that extracellular vesicles (EVs) have the potential to support hematopoietic stem and progenitor cell (HSPC) expansion; however, the mechanism and processes responsible for the intercellular communication by EVs are still unknown. In the current study, we investigate whether primary human bone marrow derived mesenchymal stromal cells (BMSC) EVs isolated from two different origins, fetal (fEV) and adult (aEV) tissue, can increase the relative low number of HSPCs found in umbilical cord blood (UCB) and which EV-derived components are responsible for ex vivo HSPC expansion. Interestingly, aEVs and to a lesser extent fEVs, showed supportive ex vivo expansion capacity of UCB-HSPCs. Taking advantage of the two BMSC sources with different supportive effects, we analyzed the EV cargo and investigated how gene expression is modulated in HSPCs after incubation with aEVs and fEVs. Proteomics analyses of the protein cargo composition of the supportive aEV versus the less-supportive fEV identified 90% of the Top100 exosome proteins present in the ExoCarta database. Gene Ontology (GO) analyses illustrated that the proteins overrepresented in aEVs were annotated to oxidation-reduction process, mitochondrial ATP synthesis coupled proton transport, or protein folding. In contrast, the proteins overrepresented in fEVs were annotated to extracellular matrix organization positive regulation of cell migration or transforming growth factor beta receptor (TGFBR) signaling pathway. Small RNA sequencing identified different molecular signatures between aEVs and fEVs. Interestingly, the microRNA cluster miR-99b/let-7e/miR-125a, previously identified to increase the number of HSPCs by targeting multiple pro-apoptotic genes, was highly and significantly enriched in aEVs. Although we identified significant differences in the supportive effects of aEVs and fEVs, RNAseq analyses of the 24hrs treated HSPCs indicated that a limited set of genes was differentially regulated when compared to cells that were treated with cytokines only. Together, our study provides novel insights into the complex biological role of EVs and illustrates that aEVs and fEVs differentially support ex vivo expansion capacity of UCB-HSPCs. Together opening new means for the application of EVs in the discovery of therapeutics for more efficient ex vivo HSPC expansion.